Effect of water exercise in blood pressure and sleep quality of hypertensive adults - Matos Fraga, Vanessa; Tanil Montrezol, Fábio; Tavares Martins, Daniele; Medeiros, Alessandra (The Journal of sports medicine and physical fitness, 2020)
Together with ageing there is an increase in blood pressure levels. However, physical activity is one of the most recommended strategies for preventing the increase of blood pressure. Water exercise involves numerous advantages, one of which is the comfort proportioned by water temperature. The aim of this study was to evaluate the effects of a water exercise program on blood pressure, physical fitness, quality of sleep and the likelihood of having sleep apnea (SA) in hypertensive adults. We evaluated 21 sedentary hypertensive subjects of both sexes. The water exercise was conducted over 13 weeks, three times/week, 50 min/day. Resting blood pressure, height, body weight, waist and hip circumference, functional capability, as well as sleep quality and the likelihood of having sleep apnea were evaluated before and after the experimental period. There was a significant decrease in systolic and mean blood pressure. Significant increases in strength, muscular and aerobic endurance, coordination, agility, dynamic balance and flexibility were also seen. In addition, a reduction in the likelihood of sleep apnea was identified, despite a deterioration in sleep quality. Water exercise was effective in reducing systolic blood pressure, in improving functional capacity variables, and in reducing probability of sleep apnea in hypertensive subjects, however it promoted worsening of sleep quality.